The content and effectiveness of physical activity for cancer‐related fatigue among colorectal cancer survivors: Systematic review and meta‐analysis - Liangrong Geng; Xiaoyu Li; Liqun Guo; Rui Zhang; Shujin Yue (Wiley, 2023)
Abstract Aims To review the content and efficacy of physical activity (PA) for cancer‐related fatigue (CRF) among colorectal cancer survivors. Design Systematic review. Methods A comprehensive search for randomized controlled trials from inception to April 1, 2022, of the following database was performed: EMBASE, PubMed, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data and China Biology Medicine (CBM). RevMan5.4 software was used for performing meta‐analysis. Results A total of eight qualified randomized controlled trials that included 542 survivors were included. PA interventions significantly reduced the CRF (SMD = −0.46; 95% CI: [−0.76, −0.15], Z = 2.67, p = 0.003); Subgroup analysis showed that fatigue was significantly improved when the length of interventions was at least 6 months and the weekly duration of PA was less than 150 min/week (SMD = −0.54; 95% CI: [−0.81, −0.27], Z = 3.87 and p = 0.0001; SMD = −0.67; 95% CI: [−1.15, −0.19], Z = 2.74 and p = 0.006); PA intervention with the length of <6 months and the volume of ≥150 min/week did not reduce fatigue (p > 0.05).